2011
DOI: 10.4081/dr.2011.e43
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband UVB-induced lichen planus pemphigoides

Abstract: Lichen planus pemphigoides (LPP) is an autoimmune disease characterised by evolution of subepidermal blisters on normal and lichen planus affected skin. We describe a case of LPP in a 54-year-old Chinese woman. The patient presented with psoriasiform plaques and was diagnosed with guttate psoriasis. Narrowband ultraviolet B (NBUVB) therapy was commenced, and she experienced a generalised eruption of violaceous papules, bullae over the lower limbs, and Wickham's striae over the buccal mucosa. Histology from a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The main adverse reactions were bullous lesion, desquamation and blister formation caused by NBUVB and topical tacrolimus. Studies have reported the bullous pemphigoid induced by PUVA therapy and NBUVB in psoriasis[2122]. Drug interactions were also checked and found five interactions, mainly with PUVASol.…”
Section: Resultsmentioning
confidence: 99%
“…The main adverse reactions were bullous lesion, desquamation and blister formation caused by NBUVB and topical tacrolimus. Studies have reported the bullous pemphigoid induced by PUVA therapy and NBUVB in psoriasis[2122]. Drug interactions were also checked and found five interactions, mainly with PUVASol.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the C-terminal portion of COL17 and desmoglein 1 have been identified as epitopes and antigens, respectively, in LPP (26). Other autoantibodies against unidentified antigens with a molecular weight of 130 kDa (27) and 200 kDa (28) have also been described. The reported variability in autoantigen specificity may result in clinical variants of LPP which appear similar to BP, with autoantibodies against NC16A (24, 29), and MMP with mucosal lesions and autoantibodies against the C-terminal portion of COL17 (26, 30).…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Psoralen ultraviolet A (PUVA) [90], narrowband ultraviolet B phototherapy (NBUVB) and photodynamic therapy (PDT) can induce typical and atypical, localized or generalized forms of BP. Rakvit et al reported a case of localized BP induced by PDT [91] and Chan et al reported a case of generalized lichen planus pemphigoides induced by NBUVB therapy [92].…”
Section: Atypical Presentations Of Bullous Pemphigoidmentioning
confidence: 99%